Scaling-up interventions to improve infant and young child feeding in India: What will it take? - Avula, Rasmi; Oddo, Vanessa M.; Kadiyala, Suneetha; Menon, Purnima (John Wiley & Sons, 2017)
We assessed India's readiness to deliver infant and young child feeding (IYCF) interventions by examining elements related to policy, implementation, financing, and evidence. We based our analysis on review of (a) nutrition policy guidance and program platforms, (b) published literature on interventions to improve IYCF in India, and (c) IYCF program models implemented between 2007 and 2012. We find that Indian policies are well aligned with global technical guidance on counselling interventions. However, guidelines for complementary food supplements (CFS) need to be reexamined. Two national programs with the operational infrastructure to deliver IYCF interventions offer great potential for scale, but more operational guidance, capacity, and monitoring are needed to actively support delivery of IYCF counselling at scale by available frontline workers. Many IYCF implementation efforts to date have experimented with approaches to improve breastfeeding and initiation of complementary feeding but not with improving diet diversity or the quality of food supplements. Financing is currently inadequate to deliver CFS at scale, and governance issues affect the quality and reach of CFS. Available evidence from Indian studies supports the use of counselling strategies to improve breastfeeding practices and initiation of complementary feeding, but limited evidence exists on improving full spectrum of IYCF practices and the impact and operational aspects of CFS in India. We conclude that India is well positioned to support the full spectrum of IYCF using existing policies and delivery platforms, but capacity, financing, and evidence gaps on critical areas of programming can limit impact at scale.